2013
DOI: 10.1371/journal.pone.0073027
|View full text |Cite
|
Sign up to set email alerts
|

High Sensitive Detection of Carbohydrate Binding Proteins in an ELISA-Solid Phase Assay Based on Multivalent Glyconanoparticles

Abstract: Improved detection of anti-carbohydrate antibodies is a need in clinical identification of biomarkers for cancer cells or pathogens. Here, we report a new ELISA approach for the detection of specific immunoglobulins (IgGs) against carbohydrates. Two nanometer gold glyconanoparticles bearing oligosaccharide epitopes of HIV or Streptococcus pneumoniae were used as antigens to coat ELISA-plates. A ~3,000-fold improved detection of specific IgGs in mice immunized against S. pneumoniae respect to the well known BSA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 43 publications
1
36
0
Order By: Relevance
“…The use of ELISAs to study protein-carbohydrate interactions has already been reported for many systems, making this assay a good choice for further development [ 43 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. Generally, a solid surface is functionalized by a layer of carbohydrates [ 53 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of ELISAs to study protein-carbohydrate interactions has already been reported for many systems, making this assay a good choice for further development [ 43 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. Generally, a solid surface is functionalized by a layer of carbohydrates [ 53 ].…”
Section: Introductionmentioning
confidence: 99%
“…12 In another study conducted by Anish and Seeberger et al, a suitable hapten from lipophosphoglycans was identified by profiling antibodies from Leishmania parasite-infected patients and animals using a microarray of synthetic oligosaccharides. In this study, Penadés group used oligomannose and a tetrasaccharide on gold nanoparticles to capture antibodies induced by HIV and S. pneumonia, respectively.…”
Section: Carbohydrate-protein Interactionsmentioning
confidence: 99%
“…Recent improvements have allowed such assays to be performed on paper-based devices for POC diagnostics. 12 In addition to pathogen detection, cancer biomarkers have been analyzed with this approach. In the example of invasive aspergillosis diagnosis, galactomannan in circulation is detected by ELISA with specific monoclonal antibodies.…”
Section: Enzyme-linked Assaysmentioning
confidence: 99%
“…Provide a tool to retain particle luminescence for applications such as extracellular sensing and imaging [23][24][25] Chitin and chitosan nano-sized polymers Biocompatible, biodegradable, and has applications in tissue engineering, wound healing, and excipients for drug delivery [26,27] Metal-based glyconanoparticles Advantages include water solubility, biocompatibility, stability, and targeting; makes use of the "glycocode" to specifically target pathogens [28][29][30][31] Functionalized fullerenes, such as Paclitaxel-embedded buckysomes Deliver an increased amount of paclitaxel, resulting in a greater anticancer efficacy [32][33][34][35] process is predicated upon the common belief that the potential likelihood for developing health risks is a function of both hazard and exposure to NPs. In essence, health risks cannot occur in the absence of individual exposures.…”
Section: Nano Risk Framework or Nanoparticle Risk Managementddevelopmmentioning
confidence: 99%